2014
DOI: 10.1021/ef402264a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarich Filtration Combustion of Ethane

Abstract: Ultrarich filtration combustion of ethane is studied in a porous medium composed of alumina spheres with the aim to achieve optimized conversion to hydrogen and syngas. Temperature, velocities, and chemical products of the combustion waves are recorded experimentally in a range of equivalence ratios ϕ from stoichiometry (ϕ = 1) to ϕ = 2.5. Experimental and numerical results are reported for 3.5 mm diameter alumina spheres; an oxygen content of the oxidizer is varied from 21 to 30%. Two temperature models based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…All propagation speeds are less than ∼0.0025 cm/s. In summary, for two fuel–air mixtures, the regimes of sub- and superadiabatic combustion also manifest themselves in the directions of the wave propagation …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All propagation speeds are less than ∼0.0025 cm/s. In summary, for two fuel–air mixtures, the regimes of sub- and superadiabatic combustion also manifest themselves in the directions of the wave propagation …”
Section: Results and Discussionmentioning
confidence: 99%
“…In summary, for two fuel−air mixtures, the regimes of sub-and superadiabatic combustion also manifest themselves in the directions of the wave propagation. 21 Figures 3 and 4 show combustion temperature and wave velocity for different oxygen contents in the air for the cases above with equivalence ratios of 4.0 and 5.0 for the two fuels. For methanol (Figure 3), the decrease in the temperature with an increasing percentage of oxygen is within experimental uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PIB is also regarded as the most promising technology for producing H 2 and syngas (H 2 + CO) from the fuel-rich combustion of gaseous and liquid hydrocarbons. ,− In order to demonstrate the influence of DME addition on the H 2 /syngas generation capability of LPG–air combustion under fuel-rich conditions, Figure reports the concentrations of H 2 , CO, and CO 2 at the PIB exit as a function of α, for the same input condition of φ = 1.3 and m = 1.5 kg/m 2 s. It is found that conversion of initial reactant to H 2 increases mildly with the addition of DME to the LPG–air mixture. However, a substantial decrease in CO mole fraction is observed with the increase of DME content in the LPG–DME mixture, causing a decline in syngas yield.…”
Section: Resultsmentioning
confidence: 99%
“…Porous media combustion is one such technology in which the fuel–air mixture is allowed to combust in a conducting and radiating porous medium. Because of improved heat transfer within the porous medium, not only can low heating value fuels be easily combusted but also a substantial improvement in combustion efficiency and better emission characteristics can be attained. Because of these unique features, porous media combustion has potential applications in internal combustion engines, , heat exchangers, radiant burners, micro burners, gas turbines and propulsion, syngas and hydrogen production, and cooking stoves. …”
Section: Introductionmentioning
confidence: 99%